IMPLEMENTASI KRACK DAN KRACK DETECTOR TERHADAP WPA_SUPPLICANT PADA PERANGKAT ANDROID DAN LINUX UBUNTU - Nanang Trianto; Dimas Febriyan Priambodo; Dozy Arti Insani (STMIK Sinar Nusantara, 2022)
Nowadays WiFi services is available in many public places to accesses the information. Most of WiFi services use the Wifi Protected Access 2 (WPA2) security. This protocol uses a 4-way handshake mechanism for authentication process, but there is a weakness by using the 4-way handshake mechanism that possible to re-install the key (KRACK). This weakness can be used by attackers to hold up communications so that attackers can enter the network. This study, KRACK analysis was carried out on wpa_supplicant Android and Linux Ubuntu which connected to WiFi and the WPA2 security protocol to know the weaknesses. The analysis is doing on the user's device by connecting to the Rogue AP generated by the Vanhoef script. This dangerous line is compared to normal line. Analyzing attacks on 4-way handshakes, this research create implementation of KRACK Detector and the result of detection will be used to get the KRACK characteristics. The information getting from the result can prevent the disadvantages which coming by attacks. The validation of the research was carried out by using Wireshark to make sure that the third massage sends which show threat of attack.